Vloga pravorečja in njegovo poučevanje v slovenskem osnovno- in srednješolskem izobraževanju - Tivadar, Hotimir (Jezik in slovstvo, 2015)
The teaching of speech and orthoepy is often neglected in Slovenia. Slovenian studies and disciplines mostly deal with written language and "written literacy", thus at best treating reading as a mechanical conversion of the written text into speech, often only through silent reading. Even when it comes to the national assessment of knowledge and the Matura exam, the emphasis is on the written examination, while speech is only indirectly given regular attention in class work and during oral exams. In this article, we present the actual presence of speech in syllabuses and text books (shown in percentages), which can serve as a basis for future work and the development of educational courses in speech and orthoepy. We must be aware of the fact that the position of Slovenian language has changed in the last few years, and that the use of Slovenian language as a first language in public in Slovenia is less self-evident than it was when Slovenia gained independence. The teaching of speech in primary and secondary schools is therefore even more important, and the role of teachers, who, especially in primary schools, function as role models, is crucial.
Keywords: Slovene; slovenščina; fonetika; phonetics; pravorečje; retorika; rhetoric; osnovne šole; srednje šole